2021
DOI: 10.1016/j.meegid.2021.105087
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the first stage of the COVID-19 pandemic in Ukraine using epidemiological and genomic data

Abstract: The novel coronavirus SARS-CoV-2 was first detected in China in December 2019 and has rapidly spread around the globe. The World Health Organization declared COVID-19 a pandemic in March 2020 just three months after the introduction of the virus. Individual nations have implemented and enforced a variety of social distancing interventions to slow the virus spread, that had different degrees of success. Understanding the role of non-pharmaceutical interventions (NPIs) on COVID-19 transmission in different setti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…To date, only one study on the phylodynamic analysis of the SARS-CoV-2 sequences obtained from Ukrainian patients has been reported, describing the first four months of the pandemic. It showed that the initial rise in the number of COVID-19 cases was likely led by multiple independent introductions of the virus into Ukraine prior to border closures 26 , similar to the findings of the importation and circulation of SARS-CoV-2 lineages in the UK 7 . For the first time, our study aimed to build local and sustainable SARS-CoV-2 sequencing capacity and genomic epidemiology expertise in Kyiv, Ukraine using the Oxford Nanopore Technology (ONT) MinION sequencing platform.…”
Section: Introductionsupporting
confidence: 61%
“…To date, only one study on the phylodynamic analysis of the SARS-CoV-2 sequences obtained from Ukrainian patients has been reported, describing the first four months of the pandemic. It showed that the initial rise in the number of COVID-19 cases was likely led by multiple independent introductions of the virus into Ukraine prior to border closures 26 , similar to the findings of the importation and circulation of SARS-CoV-2 lineages in the UK 7 . For the first time, our study aimed to build local and sustainable SARS-CoV-2 sequencing capacity and genomic epidemiology expertise in Kyiv, Ukraine using the Oxford Nanopore Technology (ONT) MinION sequencing platform.…”
Section: Introductionsupporting
confidence: 61%
“…After duplicates were removed, the titles and abstracts of 1,628 reports were reviewed by one of the authors (JFL), and 131 met the eligibility criteria (Figure 1). The current review was primarily based on 107 full papers, 2‐108 but, due to the scarcity of data, we also chose to cite five relevant abstracts 109‐113 for a more complete picture of child health in Ukraine. Our literature search was limited to papers published in English.…”
Section: Methodsmentioning
confidence: 99%
“…As the pandemic wore on the virus spread from region to region and country to country at varying rates, impacting some countries more than others 7 . For example, the first case of COVID-19 in Western Europe was confirmed on January 24, 2020 8 while the first confirmed case in Ukraine was reported on March 3, 2020 9 . The epidemic burden in various countries was also different for multiple reasons such as epidemic intensity 7 , overall preparedness of the authorities 10 and scope of implemented public health measures.…”
Section: Excess Mortality Inmentioning
confidence: 99%
“…However, the attention that has been given to Eastern Europe in general and Ukraine in particular has been limited, even though it is the 2nd largest European country by area and 7th largest by the population. The available Ukrainian studies included general epidemic response studies 22,23 , disease transmission modeling for case counts for different stages 9,[24][25][26] , genomic epidemiology analyses 9,[27][28][29] , as well as the COVID-19 vaccination campaign studies including relevant limitations such as vaccination hesitancy 30,31,[31][32][33][34] . The overall impact of the pandemic in Ukraine as determined via excess mortality studies has only been done in the global context with no country specifics or only during the early pandemic stages [35][36][37] .…”
Section: Excess Mortality Inmentioning
confidence: 99%